Hyper IgE in New Zealand black mice due to a dominant-negative CD23 mutation. - Lewis, G; Rapsomaniki, E; Bouriez, T; Crockford, T; Ferry, H; Rigby, R; Vyse, T; Lambe, T; Cornall, R (2004)
Immunoglobulin E (IgE) plays a critical role in both resistance to parasitic infection and allergy to environmental antigens. The IgE response is in turn regulated by the B-cell co-receptor CD23, and CD23-deficient mice show exaggerated IgE responses and airway hyper-responsiveness. In this report, we show that New Zealand black (NZB) mice express a variant CD23 allele, with mutations in both the C-lectin-binding domain and stalk region, which fails to bind IgE at high affinity and has reduced expression on the cell surface. Expression of the variant CD23 chain interferes with trimerisation of the receptor and has a dominant-negative effect leading to reduced IgE binding in crosses between NZB and other strains. Genetic mapping shows that the variant CD23 leads to an exaggerated primary IgE response, which is independent of other strain-specific effects. These results suggest that NZB mice or mice carrying the variant allele will be useful models for studying both allergy and quantitative traits associated with atopy. The exaggerated IgE response provides an explanation for the natural resistance of NZB mice to parasitic infection by Leishmania.